Application of Acupressure to reduce nausea and vomiting due to chemotherapy in cancer patients - Siti Utami Dewi; Agung Waluyo; Riri Maria (JIKP Jurnal Ilmiah Kesehatan PENCERAH, 2022)
Introduction: Cancer patients rate nausea and vomiting as the most unpleasant side effect of chemotherapy, even though antiemetic therapy has been given intensively. Acupressure is a non-pharmacological action that can reduce the effects of nausea and vomiting. Purpose: To determine the effectiveness of the application of acupressure on nausea and vomiting due to chemotherapy in cancer patients. Methods: This research is a literature study, articles were collected using Google Scholar, ScienceDirect, and PubMed databases with keywords acupressure, nausea, vomiting, and chemotherapy. Inclusion criteria included articles published from 2013-2022. Results: Based on a review of 10 articles discussing the application of acupressure therapy interventions that can provide effective results for reducing nausea and vomiting in cancer patients undergoing chemotherapy. Conclusion: Acupressure therapy has a significant impact in reducing nausea and vomiting in patients undergoing chemotherapy and can be used as an alternative for nursing interventions in overcoming nausea and vomiting due to chemotherapy in cancer patients.